THE OPAQUE PORTRAIT OF CORRUPTION ERADICATION - Marwan Mas (Indonesia Prime, 2016)
The war against corruption should not only by exposing the various cases of corruption, but the most important thing is to punish the corrupt in an extraordinary way to have a deterrent effect and not replicable by potential criminals that have been queued. Corruption is more structured and systematic, from the center to the regions. In fact, gave birth to a new generation of fat accounts with the discovery of a number of civil servants who are still young. Stop the robbery of money the state cannot just with rhetoric, let alone just a call that seemed hot chicken droppings. Blurred portrait of corruption is characterized by a large number of cases the defendant is acquitted of corruption Anticorruption Court. Similarly, many major cases involving alleged power elite and the ruling political party that is not completed, such as the Bank Century case, the case Hambalang project, as well as allegations of corruption Pensions SEA Games athletes